HCV and Lymphoproliferation - Anna Linda Zignego; Carlo Giannini; Laura Gragnani (Clinical and Developmental Immunology, 2012)
Hepatitis C virus (HCV) infection is a serious public health problem because of its worldwide diffusion and sequelae. It is not only a hepatotropic but also a lymphotropic agent and is responsible not only for liver injury—potentially evolving to cirrhosis and hepatocellular carcinoma—but also for a series of sometimes severely disabling extrahepatic diseases and, in particular, B-cell lymphoproliferative disorders. These latter range from benign, but prelymphomatous conditions, like mixed cryoglobulinemia, to frank lymphomas. Analogously with Helicobacter pylori related lymphomagenesis, the study of the effects of viral eradication confirmed the etiopathogenetic role of HCV and showed it is an ideal model for better understanding of the molecular mechanisms involved. Concerning these latter, several hypotheses have been proposed over the past two decades which are not mutually exclusive. These hypotheses have variously emphasized the important role played by sustained stimulation of the immune system by HCV, infection of the lymphatic cells, viral proteins, chromosomal aberrations, cytokines, or microRNA molecules. In this paper we describe the main hypotheses that have been proposed with the corresponding principal supporting data.